Snack Bar Formulation High in Antioxidants and Dietary Fiber with Substitution of Corn Flour and Spirulina Flour - Albert Johannes (Universitas Slamet Riyadi Surakarta, 2023)
Abstrak Indonesia is the sixth country with the highest number of Diabetes Mellitus sufferers in the world. One way to control blood sugar levels is to regulate a DM diet by consuming foods high in fiber and antioxidants. Snack bars are very suitable as a snack for DM sufferers. This research aims to obtain a formulation and determine the effect of adding corn flour on the antioxidant activity and dietary fiber of snack bars with the best substitutes for corn flour and spirulina flour. Research Method: This research is an experimental type of research using a completely randomized design (CRD) with independent variables in the form of a comparison of the composition of corn flour, namely F1 = corn flour 33.3% and spirulina flour 8.3%; F2= 50% corn flour and 8.3% spirulina flour and 8.3% spirulina flour; F3= 66.67% corn flour and 8.3% spirulina flour. The snack bar formulation uses wheat flour, corn flour, spirulina flour, eggs, margarine, Diabetasol powdered milk and Tropicana sugar. The steps in the procedure for making a snack bar are the preparation process, mixing process, forming or molding process, oven process, then letting it sit and serving. The analyzes used are organoleptic, antioxidant analysis, dietary fiber analysis, proximate analysis. The formulation that was acceptable to the panelists was the F3 formulation with the addition of 66.67% corn flour and 8.3% spirulina flour. The use of corn flour and the addition of spirulina flour in snack bars can increase the content of dietary fiber (9%) and antioxidants (36.16%). Comparison with the standard quality of snack bars for diets, F3 snack bars contain protein (7.89%), carbohydrates (50.38%), ash (1.2%), fat (15.20%), and energy (365 .35). The fat, carbohydrate, dietary fiber and mineral content meets the SNI 014216-1996 and USDA 5048 quality standards, while the protein content is still lacking.